Pengaruh Pengetahuan Akuntansi Dan Lama Usaha Terhadap Kualitas Laporan Keuangan Umkm Dalam Perspektif Akuntansi Syariah (Studi Kasus Di Kecamatan Tanjung Pura Kabupaten Langkat) - Raudhatul Jannah; Hotbin Hasugian; Wahyu Syarvina (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The purpose of this study was to determine the effect of accounting knowledge and length of business on the quality of MSME financial statements from a sharia accounting perspective. The method used in this research is quantitative descriptive research method, sampling is done using random sampling technique. The number of respondents reached 97 people. The results of this study indicate that educational background, length of business and business size simultaneously have a significant positive effect on the quality of MSME financial reporting. Business length and business size have a positive but insignificant effect on the quality of financial statements. And educational background has a significant positive effect on the quality of financial statements.